Global genome analysis of the shikimic acid pathway reveals greater gene loss in host-associated than in free-living bacteria - Žučko, Jurica; Dunlap, Walter C.; Shick, J. Malcolm; Cullum, John; Cercelet, François; Amin, Bijal; Hammen, Lena; Lau, Timothy; Williams, Jamal; Hranueli, Daslav; Long, Paul F. (BMC genomics, 2010)
A central tenet in biochemistry for over 50 years has held that microorganisms, plants and, more recently, certain apicomplexan parasites synthesize essential aromatic compounds via elaboration of a complete shikimic acid pathway, whereas metazoans lacking this pathway require a dietary source of these compounds. The large number of sequenced bacterial and archaean genomes now available for comparative genomic analyses allows the fundamentals of this contention to be tested in prokaryotes. Using Hidden Markov Model profiles (HMM profiles) to identify all known enzymes of the pathway, we report the presence of genes encoding shikimate pathway enzymes in the hypothetical proteomes constructed from the genomes of 488 sequenced prokaryotes.
Gesehen am 31.10.2023